Retrieving and Transferring Embodied Data: Implications for the Management of Interdependence Within Organizations - King, Andrew (Management Science, 1999)
This research helps to link theories of sticky information with organizational design and governance. It suggests that information embodied in process material can allow downstream tasks to uncover information about upstream tasks. It shows that downstream operators can use this information to negotiate interdependence problems with upstream operators. Data presented in this article begin to uncover when such information retrieval and exchange occurs, and how managers can encourage it. Finally, the article discusses implications for theories of operational design and governance.